Peran Komite Madrasah Dalam Penyusunan Rencana Kerja Madrasah Di Madrasah Tsanawiyah Nurul Qona'ah - Aditia, Bambang Eko (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2017)
The roles of the madrasah committee are so complicated, that one of its roles is in the arrangement of RKM, and for this case, it includes the role of an advisory agency, a supporting agency, a controlling agency, and a mediator. RKM is a madrasah document written related to the madrasah development plan in the future which for this arrangement process has to involve the whole parties related to the madrasah, including the committee. As the application of a qualitative research procedure, the study was concluded as follows: the first; the roles of the madrasah committee as the advisory agency in the arrangement of RKM in MTs Nurul Qana’ahMumbulsari. The second, the role of supporting agency was conducted by the committee MTs Nurul Qana’ah Mumbulsari through supporting: 1) madrasah in extracurricular activities, 2) madrasah in arranging the local content subject, 3) madrasah in improving the average score of madrasah for national examination, 4) madrasah in national examination funding, 5) madrasah in the instructional of English and Computer Information Science, 6) madrasah in making madrasah fence, 7) madrasah to dun infak (alms) for the students. The third, the role of the committee as the controlling agency in the arrangement of RKM and MTs Nurul Qana’ahMumbulsari involves supervising and controlling: 1) the process of fence making, 2) the process of additional instructional to face national examination and its funding, 3) the computer supply program, 4) the use of national examination fund, 5) the fund use planned to supply computers, 6) the process of officer recruitment, 7) the extracurricular program, 8) the arrangement of curriculum, 9) the process of decreasing the number of drop-out students, 10) the types of fund sources Keywords: the roles of the madrasah committee, the RKM, and the arrangement